The effect of cooperative model type STAD assisted by interactive learning media on students' understanding of mathematical concepts - Asmini Mahadi; tedy machmud; Khardiyawan A.Y. Pauweni (Universitas Sarjanawiyata Tamansiswa, 2023)
The study's goal was to see how the cooperative learning model STAD type aided by interactive learning media in terms of students' understanding of mathematical concepts in algebra material at SMP Negeri 1 Suwawa. With 25 students per class were determined using the experimental research post-test only control group design with two classes as a research sample and simple random sampling. As a result, students' ability to understand mathematical concepts in the STAD type cooperative class is higher than in the control class's direct learning model. This is demonstrated by the mean value of students' ability to understand mathematical concepts in the STAD type cooperative model class, which is 70.36 compared to 63.48 in the control class. The inferential analysis using the t test revealed that H0 was rejected because tcount = 1.916 > ttable = 1.68. To summarize, the ability of students' concepts in the STAD type cooperative model class assisted by articulate storyline media is greater than in the direct learning model class.